MENINGKATKAN KETERAMPILAN PROSES SAINS DAN HASIL BELAJAR MELALUI MODEL INKUIRI KELAS VII DI SMP - Dela, Dela; Tandililing, Edy; B Arsyid, Syaiful (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This study is aimed to find out whether there is an increase of students' science processes skill and student achievement through inquiry model in sub-material changes in the form of substance class VII in SMP Negeri 2 Pontianak. The method used in this research is experimental method with Pre-Experimental Design with One-Group-Pretest-Posttest Design. The population is the students of class VII SMP Negeri 2 Pontianak which consists of seven classes. The sampling technique used is intac group. Thus the sample of this study was conducted on 28 students of class VII in one SMP Negeri 2 Pontianak. The tool of data collection of this research includes the test of description questions for student learning achievement and student worksheets of science process skills for student performance test. The result of this research shows that there is an improvement of students' science process skill and student learning achievement through inquiry model in sub-material changes in the form substance (P-Value <0,05).Keywords: Process sains skill, learning achievement, inquiry model